Capacitación laboral y su influencia en el servicio de atención al cliente - Bitel Perú, Cercado de Lima - 2017 - De la Cruz Encalada, Daniel Andrés (2017)
The problem of poor training is determined by a conflict between the activities carried out by people generally produced by the environment, which covers all of them. The causes of this problem, its effects and what may happen, however, it is important to have ready to help others to face an activity that threatens or deserves. Some situations that can help to counteract this problem is the satisfaction of a job well done and the good remuneration due that helps a problem that has been attacking employees. We can determine that this problem is presented by all companies in due time each and for that we must be ready to face it.